Quasi-periodic oscillations around compact objects within the Sen spacetime - Konysbayev, T.; Kurmanov, Ye.; Nurlanbek, U.; Rabigulova, G.; Adil, M.; Bekmurat, B.; Tuzen, G.; Urazalina, A. (Recent Contributions to Physics, 2026)
We investigate kilohertz (kHz) quasi-periodic oscillations (QPOs) observed in eight neutron-star low-mass X-ray binaries within the framework of the relativistic precession model (RPM). Fundamental (epicyclic) frequencies of test particles on circular orbits are computed in the static Sen spacetime. By fitting the Keplerian and epicyclic frequencies to the observed lower and upper QPO frequency pairs, (fU, fL) we infer the masses and electric charges of the compact objects and compare the results with those obtained in the Schwarzschild spacetime using the Akaike and Bayesian information criteria (AIC/BIC). We find that the Schwarzschild geometry provides physically consistent fits for four sources, while for GX 5–1 and GX 340+0 the Sen spacetime becomes effectively indistinguishable from Schwarzschild, indicating that no electric charge is required. Although the Sen metric yields statistically improved fits for the remaining four sources, the inferred large masses as well as large electric charges are incompatible with neutron-star physics. We therefore conclude that the static Sen spacetime does not provide a physically viable description of kHz QPOs in neutron-star systems.